A case report of retroperitoneal dedifferentiated chondrosarcoma with femoral nerve involvement - Satya Prakash, Shalinee; Kumar, Ashok; Talwar, Nikhil; Moeenuddeen; Goel, Mahak (International Journal of Research in Medical Sciences, 2025)
Chondrosarcomas, a type of malignant bone tumour, are relatively rare and originate from cartilage producing cells. Dedifferentiated chondrosarcoma (DDCS), which makes up about 10% of all chondrosarcomas, is a rare and extremely aggressive subtype with high risk of metastasis. Here we report a case of 60-year-old lady with left lower abdomen lump of 10x10cm since 5months with normal gait, normal sensory, motor, spine and hip examination which shows no bony involvement in X-rays. On CECT and MRI there was large heterogenous enhancing soft tissue density mass lesion of size 11.7×10.9 cm with multiple coarse calcifications, without bone involvement. On Ultrasound guided core needle biopsy, it was found to be low grade chondrosarcoma. Patient was planned for wide local excision of tumor with adequate margins. Intraoperatively femoral nerve was seen passing inside the tumor which was resected and nerve repair done with sural nerve graft. In Post operative period patient had difficulty in extending left leg so knee gaiter was advised for support. After 6months follow up patient was seen healthy and walking without knee gaiter. Dedifferentiated chondrosarcoma (DDCS), which makes up about 10% of all chondrosarcomas, is a rare and extremely aggressive subtype. It is associated with high rates of metastasis and poor survival. Surgery is generally the standard of care for patients and adequate margins are recommended. Role of chemoradiotherapy is controversial. Surgery is the treatment of choice in dedifferentiated chondrosarcoma in patients with local disease with no metastasis.